Effects of rainfall deviations on non-farm labour market participation and time allocation in northern Ghana. Issue 7 (2nd October 2020) - Asravor, Richard Kofi
ABSTRACT: This article analyses the effects of rainfall deviations on households' non-farm decisions and time allocations in northern Ghana, drawing on a sample of 500 farm households. Using the double hurdle approach, the article shows that rainfall deviations affected decisions to participate in non-farm work, but not the hours allocated to non-farm work. Age and membership of farmer-based organisations were important factors in non-farm decisions, while educational level and the number of adults in the household determined the time allocated to non-farm work. It is recommended that policies on non-farm work for rural farm households in northern Ghana should take climate variables into consideration.